2021
DOI: 10.1007/978-3-030-81242-3_10
|View full text |Cite
|
Sign up to set email alerts
|

Access Control Policy Generation from User Stories Using Machine Learning

Abstract: Agile software development methodology involves developing code incrementally and iteratively from a set of evolving user stories. Since software developers use user stories to write code, these user stories are better representations of the actual code than that of the highlevel product documentation. In this paper, we develop an automated approach using machine learning to generate access control information from a set of user stories that describe the behavior of the software product in question. This is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Used in # of studies Percentage SVM [51], [39], [56], [65], [46], [64], [40], [59], [38], [74], [8], [75], [62], [76], [77], [37] 16 25 % RF [50], [41], [44], [26], [64], [29], [59], [60], [10], [33], [34], [13], [37], [69] 14 22 % DT [9], [42], [25], [71], [72], [49], [66], [33], [77] 9 14 % KNN [41], [45] , [46], [66], [59], [10] [8], [77], [43], [70], [73], S15, [53],…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Used in # of studies Percentage SVM [51], [39], [56], [65], [46], [64], [40], [59], [38], [74], [8], [75], [62], [76], [77], [37] 16 25 % RF [50], [41], [44], [26], [64], [29], [59], [60], [10], [33], [34], [13], [37], [69] 14 22 % DT [9], [42], [25], [71], [72], [49], [66], [33], [77] 9 14 % KNN [41], [45] , [46], [66], [59], [10] [8], [77], [43], [70], [73], S15, [53],…”
Section: Methodsmentioning
confidence: 99%
“…Metrics like AUC, ROC, and FNR were employed in two studies each, and the remaining metrics were reported only once. It is important to note that multiple [23], [41], [44], [53], [45], [24], [42], [70], [39], [56], [46], [26], [71], [64], [40], [28], [43], [66], [10], [30], [31], [47], [62], [33], [76], [13], [37], [67] 28 45 % Accuracy [52], [53], [70], [39], [65], [12], [71], [72], [64], [40], [57], [28], [43], [66], [59], [10], [61], [38], [48], [8], [62],…”
Section: H Performance Metrics (Rq8)mentioning
confidence: 99%
“…To address this issue, [10] designed a verified stateless firewall policy compiler, but this compiler can only perform semantic generation for specific security policies and requires reprocessing of data when dealing with security policies of other syntaxes. With the development of big data and artificial intelligence technologies, security policies are gradually relying on these technologies for optimization and automatic generation [16]. The accuracy of semantic generation is crucial when generating semantics for many different types of security policies.…”
Section: Related Workmentioning
confidence: 99%
“…Through evaluation experiments, the models presented good results. To further automate the access control mechanism, the authors of [37] leveraged a transformer-based deep learning approach to extract the access control policies from user and business stories. The authors argued that agile software development involves the user stories to incrementally develop the system, and the same idea can be employed to automate the policy specification.…”
Section: Literature Reviewmentioning
confidence: 99%